Controversies in Midday Water Potential Regulation and Stomatal Behavior Might Result From the Environment, Genotype, and/or Rootstock: Evidence From Carménère and Syrah Grapevine Varieties - Villalobos-González, Luis; Muñoz-Araya, Mariana; Franck, Nicolas; Pastenes, Claudio (Frontiers in Plant Science, 2019)
Controversies exist regarding the iso/anisohydric continuum for classifying plant water use strategies. Isohydricity has been argued to result from a plant-environment interaction, rather than an intrinsic property of the plant. Discrepancies remains regarding the degree of isohydricity () of plants and their threshold for physiological responses and resistance to drought. Thus, the aim of this study was to evaluate the isohydricity of the grapevine varieties Syrah and Carménère through a non-lethal water deficit progression from veraison on different locations: Cachapoal Valley (CV) and Maipo Valley (MV), in central Chile, and with different rootstock only in Syrah. For this purpose, the midday water potential (md) regulation and stomatal responses to drought, leaf traits related to pressure-volume curves, stomatal sensitivity to ABA, cavitation threshold and photosynthetic responses were assessed. A higher atmospheric water demand was observed in the CV compared to the MV, with lower md values in the former for both varieties. Also, the values in Carménère were 1.11  0.14 MPa MPa-1 and 0.68  0.18 MPa MPa-1 in the CV and MV, respectively, and in Syrah was 1.10  0.07 MPa MPa-1 in the CV and 0.60  0.10 MPa MPa-1 in the MV. Even though similar variations in between locations in both varieties were evident, Carménère plants showed a conserved stomatal response to md in both study sites, while those of Syrah resulted in a higher stomatal sensitivity to md in the site of lower . Besides the differences in seasonal weather conditions, it is likely that the different rootstock and clonal variability on each season in Syrah was able to induces coordinated changes in gs12 and osmotic potential at full turgor (0). On the other hand, irrespective of the , and given the similarity between the 0 and gs12 in leaves before drought, it seems that0 could be a convenient tool for assessing the md threshold values posing a risk to the plants, in order to aid the irrigation decision making in grapevines under controlled water deficit. Finally, water deficit in vineyards might be irreversibly compromising the photosynthetic capacity of leaves.